Decreasing waiting time for treatment before and during implementation of cancer patient pathways in Norway. (August 2019) - Nilssen, Yngvar; Brustugun, Odd Terje; Tandberg Eriksen, Morten; Gulbrandsen, Johanne; Skaaheim Haug, Erik; Naume, Bjørn; Møller, Bjørn
Highlights: Trends towards a more advantageous stage distribution in 2007–2016 in Norway. Cancer patient pathways were implemented in Norway in 2015. Significant reductions in waiting time from diagnosis to treatment. Decreased differences in waiting time to treatment between health regions. Abstract: Background: In 2015, Norway implemented cancer patient pathways to reduce waiting times for treatment. The aims of this paper were to describe patterns in waiting time and their association with patient characteristics for colorectal, lung, breast and prostate cancers. Methods: National, population-based data from 2007 to 2016 were used. A multivariable quantile regression examined the association between treatment period, age, stage, sex, place of residence, and median waiting times. Results: Reduction in median waiting times for radiotherapy among colorectal, lung and prostate cancer patients ranged from 14 to 50 days. Median waiting time for surgery remained approximately 21 days for both colorectal and breast cancers, while it decreased by 7 and 36 days for lung and prostate cancers, respectively. The proportion of lung and prostate cancer patients with metastatic disease at the time of diagnosis decreased, while the proportion of colorectal patients with localised disease and patients with stage I breast cancer increased (p < 0.001). After adjusting for case-mix, a patient's place of residence was significantly associated with waiting time for treatment (p < 0.001), however, differences in waiting time to treatment decreased over the study period. Conclusions: Between 2007 and 2016, Norway experienced improved stage distributions and consistently decreasing waiting times for treatment. While these improvements occurred gradually, no significant change was observed from the time of cancer patient pathway implementation.